An intelligent switching scheme to improve the reliability of power distribution network communication - XU Tao; XU Sheng; QUAN Hanbin; HONG Huanhua; HOU Jingying; CHEN Xiaohui; SU Lei; WU Shifan; DENG Yazhi (Dianxin kexue)
The access methods for terminal communication on the distribution network side are diverse. However, due to the lack of complete interconnection among various communication methods, the reliability of communication is compromised. Therefore, it is of great significance to realize automatic switching of various communication access modes and multi-network integration of terminals to improve the reliability of distribution communication network. Based on the research on the wide application of mature technologies such as bidirectional forwarding detection (BFD) link bidirectional monitoring, single-pole double-throw isolation, Bypass technology and tunnel technology in communication networks, the key technologies and integration methods to improve the reliability of distribution network were put forward， and the feasibility of the proposed scheme was verified by building a physical simulation environment. The simulation results show that the proposed scheme can be well applied to the complex distribution network, so as to improve its self-healing ability, meet the requirements of physical isolation and service transmission delay, and improve the reliability of the entire distribution network.